Magnetic lubricating grease and preparation method thereof
By using polya-olefin base oil, polyester compound and homemade graphene polar composite agent in the grease, a stable polar mesh oil film is solved, and the problem of grease becoming thinner and loss under high shear conditions is solved. Its wear resistance, lubrication and rust resistance are significantly improved.
Patent Information
- Application Number
- CN202311034278.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-21
AI Technical Summary
Existing greases are prone to thinning loss under high shear conditions, and their wear resistance and high temperature performance are insufficient, making it difficult to meet the requirements of use under harsh conditions.
Polya-olefin base oil and polyester compounds are used as the main components, and the homemade graphene polar composite agent is uniformly dispersed in the base oil to form a stable polar mesh oil film, which improves the extreme pressure and wear resistance of the grease. Lubrication and anti-rust effect.
It achieves excellent shear stability, thermal stability and high and low temperature performance of grease, significantly improves extreme pressure wear resistance, lubrication, rust and thermal conductivity, and extends the service life of the equipment.
Smart Images

Figure BDA0004398470750000021 
Figure BDA0004398470750000041 
Figure BDA0004398470750000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grease preparation, and in particular to magnetic grease and a preparation method thereof. Background Art
[0002] Grease is a solid or semi-fluid product in which a thickener is dispersed in a liquid lubricant. Other components (such as additives, fillers, etc.) can also be added to give it special properties. In order to meet the requirements of use under harsh conditions, suitable additives can be added to the grease to improve the application performance of the grease. It is used in the friction part of the machinery to lubricate and seal, and is also used on the metal surface to fill gaps and prevent rust. The application field of grease is very wide, covering almost all industrial machinery, agricultural machinery, transportation industry, aerospace industry, electronic information industry and various military equipment.
[0003] The Chinese patent with the announcement number CN102433203A discloses a lithium-based grease composition and a preparation method thereof, comprising 85-96% base oil; 3-14% thickener; 0.5% antioxidant; 0.5% tackifier, wherein the tackifier is polyisobutylene or polymethacrylate or ethylene-propylene copolymer. The Chinese patent with the announcement number CN103468357B discloses a water-resistant extreme pressure lithium-based grease and a preparation method thereof, comprising the following components: 70-90% base oil, 9-15% fatty acid, 1-2% lithium hydroxide, 0.3-0.7% calcium hydroxide powder, 0.1-0.5% antioxidant, 0.3-1.5% rust inhibitor, 2-5% extreme pressure agent, 2-5% tackifier, wherein the tackifier is at least one of polyisobutylene and ethylene-propylene copolymer. The Chinese patent with the announcement number CN100358987C discloses a high extreme pressure lithium-based grease, which includes 78-81 parts of high viscosity mineral oil, 7-10 parts of fatty acid, 0.9-1.5 parts of lithium hydroxide, 0.3-0.5 parts of calcium hydroxide, 0.5-1.5 parts of antioxidant, 3-6 parts of extreme pressure agent, 2-5 parts of oiliness agent, and 2-5 parts of thickener, wherein the thickener is random polypropylene. The above disclosed prior art all adopts the method of adding thickener to the grease. These polymers have good compatibility with base oil as thickeners. They are added in the later stage of grease production and dissolved in the base oil, thereby increasing the viscosity of the base oil. However, the shear resistance is poor, and the grease is easy to thin and flow under high shear conditions.
[0004] The Chinese patent with announcement number CN102229844A discloses a molybdenum disulfide lithium-based grease and its preparation method, which includes the following components and weight proportions: 70-90 parts of 12-hydroxystearic acid; 15-25 parts of stearic acid; 10-115 parts of lithium hydroxide; 1-5 parts of calcium hydroxide; 850-950 parts of base oil; 50-70 parts of additives. The preparation method is to mix and gradually increase the temperature, and finally adjust the cone penetration. The grease prepared by this preparation method has poor high temperature performance and anti-wear performance.
[0005] Therefore, it is particularly important to produce a magnetic grease with excellent shear stability and extreme pressure anti-wear properties. Summary of the invention
[0006] The purpose of the present invention is to overcome the technical defects mentioned above and to provide a magnetic grease having excellent shear stability, thermal stability and high and low temperature performance, which can form a stable polar network oil film, provide excellent extreme pressure anti-wear, lubrication and rust prevention effects; and is not easily demagnetized at high temperatures, and has excellent extreme pressure anti-wear performance, thermal conductivity and sealing performance, and a preparation method thereof.
[0007] A magnetic lubricating grease of the present invention is realized in this way, and its formula is as follows in parts by weight:
[0008]
[0009] The poly-a-olefin base oil has a kinematic viscosity of 120 to 480 centistokes at 40°C and a viscosity index of more than 140; the polyester compound is a mixture of trimethylolpropane ester and polyol ester, the kinematic viscosity of the polyester compound is between 38 and 36 centistokes at 40°C and a viscosity index of more than 130, and in the polyester compound, the weight ratio of trimethylolpropane ester to polyol ester is 2-4:6-8.
[0010] The thickener is produced by reacting fatty acids with alkali metals. Preferably, the weight ratio of the fatty acids to the alkali metals is 0.2-0.5:1-2. The fatty acids include hydrogenated castor oil, dodecyl hydroxystearic acid, stearic acid, and palmitic acid. Preferably, among the fatty acids, the weight ratio of hydrogenated castor oil, dodecyl hydroxystearic acid, stearic acid, and palmitic acid is 5-8:2-4:1-2:1-2. The alkali metals include calcium hydroxide and lithium hydroxide monohydrate. Preferably, among the alkali metals, the weight ratio of calcium hydroxide to lithium hydroxide monohydrate is 0.5-1:1-2.
[0011] The self-made graphene polar composite agent is achieved as follows:
[0012] According to weight ratio, add 40% extreme pressure anti-wear agent, 8% antioxidant, 20% dispersant, 6% rust inhibitor, 3% surfactant, 3% graphene magnetic nanopowder, and 20% low-viscosity hydrogenated base oil into the reactor, stir and heat to 50-70°C, keep the temperature at 50-70°C and continue stirring and mixing for 2-6 hours, then keep the temperature at 50-70°C for ultrasonic dispersion for 8-12 hours, and you can get the self-made graphene polar composite.
[0013] Preferably, the extreme pressure anti-wear agent comprises triphenyl thiophosphate, thiophosphate ester, ammonium thiophosphate salt, sulfided olefin, and thioamino ester. Preferably, in the extreme pressure anti-wear agent, the weight ratio of triphenyl thiophosphate, thiophosphate ester, ammonium thiophosphate salt, sulfided olefin, and thioamino ester is 1-3:5-8:1-2:1-2:1-1.5.
[0014] Preferably, the antioxidant comprises alkyl diphenylamine, phenyl-β-naphthylamine and 2,6-di-tert-butyl-p-cresol. Preferably, in the antioxidant, the weight ratio of alkyl diphenylamine, phenyl-β-naphthylamine and 2,6-di-tert-butyl-p-cresol is 4-7:2-4:1-2.
[0015] Preferably, the rust inhibitor comprises butylene diacid, oleic acid glycol ester, pentaerythritol monooleate and 1,2,3-trimethylbenzotriazole. Preferably, in the rust inhibitor, the weight ratio of butylene diacid, oleic acid glycol ester, pentaerythritol monooleate and 1,2,3-trimethylbenzotriazole is 2-6:3-5:1-3:1-2.
[0016] Preferably, the surfactant comprises sodium dodecylbenzene sulfonate, oleic acid and maleic anhydride. Preferably, in the surfactant, the weight ratio of sodium dodecylbenzene sulfonate, oleic acid and maleic anhydride is 4-6:2-5:1-2.
[0017] Preferably, the dispersant comprises boronated polyisobutylene polysuccinimide, monosuccinimide ashless dispersant and benzylamine. Preferably, in the dispersant, the weight ratio of boronated polyisobutylene polysuccinimide, monosuccinimide ashless dispersant and benzylamine is 2-6:3-5:1-3.
[0018] The preparation method of the magnetic grease comprises the following steps:
[0019] (1) 1 / 2 of the formula amount of poly-α-olefin base oil and polyester compound and 1 / 2 of the formula amount of self-made graphene polar composite agent are mixed uniformly according to the ratio, and the temperature is raised to 70-80° C.;
[0020] (2) adding a formula amount of hydrogenated castor oil, dodecyl hydroxystearic acid, stearic acid, and palmitic acid into a reaction kettle, heating to melt, and mixing evenly, and then adding a formula amount of calcium hydroxide, lithium hydroxide monohydrate, and water, mixing evenly, performing saponification reaction, and after high-temperature dehydration, cooling to 70-80° C., thereby preparing a thickener;
[0021] (3) The thickener obtained in step (2) is added to the mixture obtained in step (1), and the mixture is stirred and mixed at 70-80° C. to form a uniform emulsion. The remaining poly-α-olefin base oil, polyester compound and self-made graphene polar composite agent are added, mixed evenly, and degassed and filtered by a homogenizer to obtain a finished product.
[0022] The magnetic grease of the present invention has the following beneficial effects:
[0023] 1. Using poly-a-olefin base oil and polyester compounds, the magnetic grease has excellent shear stability, thermal stability and high and low temperature performance, can form a stable polar network oil film, and provide excellent extreme pressure anti-wear, lubrication and rust prevention effects;
[0024] 2. The self-made graphene polar composite has excellent dispersibility and compatibility in the base oil. Graphene is evenly dispersed on the polar mesh oil film, which can enhance the thermal conductivity of the polar mesh oil film and effectively help the equipment dissipate heat. Since the polar mesh oil film is adsorbed on the surface of the metal friction pair like a magnet, it is equivalent to giving the polar mesh oil film magnetism, thereby improving the adhesion and stability of the mesh oil film, reducing the friction coefficient, and significantly extending the service life of the equipment. DETAILED DESCRIPTION
[0025] The following examples illustrate the present invention, but the present invention is not limited to these examples. Modifications to the specific embodiments of the present invention or equivalent replacement of some technical features without departing from the spirit of the present invention should be included in the scope of the technical solution claimed by the present invention.
[0026] The homemade graphene polar composite is achieved as follows:
[0027] According to weight ratio, add 40% extreme pressure anti-wear agent, 8% antioxidant, 20% dispersant, 6% rust inhibitor, 3% surfactant, 3% graphene magnetic nanopowder, and 20% low-viscosity hydrogenated base oil into the reactor, stir and heat to 60°C, keep the temperature at 60°C and stir and mix for 5.5 hours, then keep the temperature at 60°C for ultrasonic dispersion for 10 hours to obtain the self-made graphene polar composite.
[0028] Example 1
[0029] This embodiment provides a method for preparing magnetic grease:
[0030] The formula includes the following components in proportion by weight: 68 parts of poly-a-olefin base oil, 8 parts of polyester compound, 15 parts of thickener, 1.2 parts of homemade graphene polar composite agent, and 7.8 parts of deionized water.
[0031] The specific preparation steps are as follows:
[0032] (1) 1 / 2 of the formula amount of poly-α-olefin base oil and polyester compound and 1 / 2 of the formula amount of self-made graphene polar composite agent were put into a reaction kettle according to the ratio, the temperature was raised to 80° C., and stirred and mixed for 60 minutes;
[0033] (2) 8 parts by weight of hydrogenated castor oil, 12 parts by weight of dodecyl stearic acid, 6 parts by weight of stearic acid, and 4 parts by weight of palmitic acid are added to a reaction kettle, heated to 95° C. to melt the fatty acids, stirred and mixed for 15 minutes, and then 10 parts by weight of calcium hydroxide, 20 parts by weight of lithium hydroxide monohydrate and a formula amount of ionized water are added, the temperature is maintained at 95° C., stirred and mixed for 45 minutes, and a saponification reaction is carried out. After the saponification reaction is completed, the temperature is raised to 180° C., dehydrated for 15 minutes, and cooled to 80° C. to obtain a thickener;
[0034] (3) The thickener obtained in step (2) is added to the mixture obtained in step (1), and the remaining poly-a-olefin base oil, polyester compound and homemade graphene polar composite agent are added. The temperature is maintained at 80° C. and stirred for 60 minutes. After degassing and filtering by a homogenizer, the finished product is obtained.
[0035] Example 2
[0036] This embodiment provides a method for preparing magnetic grease:
[0037] The formula weight ratio includes the following components: 74 parts of poly-α-olefin base oil, 6 parts of polyester compound, 13 parts of thickener, 2.2 parts of self-made graphene polar composite agent, and 4.8 parts of deionized water. The specific preparation steps are the same as those in Example 1.
[0038] Example 3
[0039] This embodiment provides a method for preparing magnetic grease:
[0040] The formula weight ratio includes the following components: 65 parts of poly-α-olefin base oil, 10 parts of polyester compound, 16 parts of thickener, 3 parts of self-made graphene polar composite agent, and 6 parts of deionized water. The specific preparation steps are the same as in Example 1.
[0041] Comparative Example 4
[0042] Commercially available No. 2 calcium-lithium complex grease.
[0043] The relevant performance test results of a magnetic grease obtained in Examples 1 to 3 and Comparative Example 4 are shown in Table 1 below.
[0044] Table 1
[0045]
[0046]
[0047] It can be seen from the above table that compared with the prior art (Comparative Example 4), the magnetic grease of the present invention has a high dropping point, a small change rate of cone penetration after extended working, excellent shear stability, thermal stability and high and low temperature performance, and the polar network oil film provides excellent extreme pressure anti-wear performance, lubrication, corrosion protection, thermal conductivity and sealing performance, which can reduce the friction coefficient of the friction pair surface, effectively help the equipment to dissipate heat and reduce wear, and significantly extend the service life of the equipment.
[0048] Main material information
[0049] 1. Poly-a-olefin base oil, industrial grade, supplied by Shanghai Nak Lubrication Technology Co., Ltd.;
[0050] 2. Hydrogenated castor oil, dodecyl stearic acid, stearic acid, palmitic acid, technical grade, commercially available;
[0051] 3. Calcium hydroxide, lithium hydroxide monohydrate, industrial grade, commercially available;
[0052] 4Trimethylolpropane ester and polyol ester, the supplier is Hangzhou Youmi Chemical Co., Ltd.;
[0053] 5. Low viscosity hydrogenated base oil, industrial grade, supplied by Formosa Petrochemical Corporation;
[0054] 6. triphenyl thiophosphate, thiophosphate esters, ammonium thiophosphate salts, sulfided olefins, thioamino esters, industrial grade, commercially available; 7. alkyl diphenylamine, phenyl-β-naphthylamine, 2,6-di-tert-butyl-p-cresol, industrial grade, commercially available;
[0055] 8. Ethylene dicarboxylic acid, oleic acid glycol ester, pentaerythritol monooleate, 1,2,3-trimethylbenzotriazole, industrial grade, commercially available; 9. Sodium dodecylbenzene sulfonate, oleic acid, maleic anhydride, industrial grade, commercially available;
[0056] 10. Borated polyisobutylene polysuccinimide, monosuccinimide ashless dispersant, benzylamine, technical grade, commercially available;
[0057] 11. Graphene magnetic nanopowder, industrial grade, commercially available.
Claims
1. A magnetic grease, characterized in that: The proportion of each component by weight is:
2. A magnetic grease as claimed in claim 1, characterized in that: The poly-a-olefin base oil has a kinematic viscosity of 120 to 480 centistokes at 40°C and a viscosity index of more than 140; the polyester compound is a mixture of trimethylolpropane ester and polyol ester, the kinematic viscosity of the polyester compound is between 38 and 36 centistokes at 40°C and a viscosity index of more than 130, and in the polyester compound, the weight ratio of trimethylolpropane ester to polyol ester is 2-4:6-8.
3. A magnetic grease as claimed in claim 1, characterized in that: The thickener is generated by reacting fatty acids with alkali metals, the weight ratio of the fatty acids to the alkali metals is 0.2-0.5:1-2, the fatty acids include hydrogenated castor oil, dodecyl hydroxystearic acid, stearic acid, and palmitic acid, and the weight ratio of hydrogenated castor oil, dodecyl hydroxystearic acid, stearic acid, and palmitic acid is 5-8:2-4:1-2:1-2; the alkali metals include calcium hydroxide and lithium hydroxide monohydrate, and the weight ratio of calcium hydroxide to lithium hydroxide monohydrate is 0.5-1:1-2.
4. A magnetic grease as claimed in claim 1, characterized in that: The self-made graphene polar composite agent is achieved as follows: According to weight ratio, add 40% extreme pressure anti-wear agent, 8% antioxidant, 20% dispersant, 6% rust inhibitor, 3% surfactant, 3% graphene magnetic nanopowder, and 20% low-viscosity hydrogenated base oil into the reactor, stir and heat to 50-70°C, keep the temperature at 50-70°C and continue stirring and mixing for 2-6 hours, then keep the temperature at 50-70°C for ultrasonic dispersion for 8-12 hours, and you can get the self-made graphene polar composite.
5. The self-made graphene polar composite agent as claimed in claim 4, characterized in that, The extreme pressure anti-wear agent includes triphenyl thiophosphate, thiophosphate ester, ammonium thiophosphate salt, sulfided olefin, and thioamino ester. In the extreme pressure anti-wear agent, the weight ratio of triphenyl thiophosphate, thiophosphate ester, ammonium thiophosphate salt, sulfided olefin, and thioamino ester is 1-3:5-8:1-2:1-2:1-1.
5.
6. The self-made graphene polar composite agent as claimed in claim 4, characterized in that The antioxidant comprises alkyl diphenylamine, phenyl-β-naphthylamine and 2,6-di-tert-butyl-p-cresol. In the antioxidant, the weight ratio of alkyl diphenylamine, phenyl-β-naphthylamine and 2,6-di-tert-butyl-p-cresol is 4-7:2-4:1-2.
7. The self-made graphene polar composite agent as claimed in claim 4, characterized in that, The rust inhibitor comprises butylene diacid, oleic acid glycol ester, pentaerythritol monooleate and 1,2,3-trimethylbenzotriazole. In the rust inhibitor, the weight ratio of butylene diacid, oleic acid glycol ester, pentaerythritol monooleate and 1,2,3-trimethylbenzotriazole is 2-6:3-5:1-3:1-2.
8. The self-made graphene polar composite agent as claimed in claim 4, characterized in that, The surfactant comprises sodium dodecylbenzene sulfonate, oleic acid and maleic anhydride. In the surfactant, the weight ratio of sodium dodecylbenzene sulfonate, oleic acid and maleic anhydride is 4-6:2-5:1-2.
9. The self-made graphene polar composite agent as claimed in claim 4, characterized in that, The dispersant comprises boronated polyisobutylene polysuccinimide, monosuccinimide ashless dispersant and benzylamine. In the dispersant, the weight ratio of boronated polyisobutylene polysuccinimide, monosuccinimide ashless dispersant and benzylamine is 2-6:3-5:1-3.
10. The magnetic grease according to claim 1, characterized in that: The preparation method comprises the following steps: (1) 1 / 2 of the formula amount of poly-α-olefin base oil and polyester compound and 1 / 2 of the formula amount of self-made graphene polar composite agent are mixed uniformly according to the ratio, and the temperature is raised to 70-80° C.; (2) adding a formula amount of hydrogenated castor oil, dodecyl hydroxystearic acid, stearic acid, and palmitic acid into a reaction kettle, heating to melt, and mixing evenly, and then adding a formula amount of calcium hydroxide, lithium hydroxide monohydrate, and deionized water, mixing evenly, performing saponification reaction, and after high-temperature dehydration, cooling to 70-80° C., thereby preparing a thickener; (3) The thickener obtained in step (2) is added to the mixture obtained in step (1), and the mixture is stirred and mixed at 70-80° C. to form a uniform emulsion. The remaining poly-α-olefin base oil, polyester compound and self-made graphene polar composite agent are added and mixed uniformly. The mixture is degassed and filtered by a homogenizer to obtain a finished product.
Citation Information
Patent Citations
High extreme pressure lithium base lubricating grease
CN100358987C
Grease based on molybdenum disulfide lithium and preparation method thereof
CN102229844A
Lithium-based lubricating grease composition and preparation method
CN102433203A
A kind of water-resistant extreme pressure lithium base lubricating grease and preparation method thereof
CN103468357B